Questioning for classroom discussion : purposeful speaking, engaged listening, deep thinking - Walsh, Jackie Acree (ASCD, 2015)
Quality questioning: the heart of thoughtful discussion -- The DNA of productive discussion: social, cognitive, and use-of-knowledge skills and companion -- Dispositions -- Teacher-guided discussion: teachers as coaches during five stages of discussion -- Structured small-group discussion: using protocols to scaffold skills for discussion -- Student-driven discussion: putting students in the driver's seat -- Questioning for discussion: creating your own designs.